Predictive validity of a nine minute run to peak VO2 in children aged 11-14 - Morsch, Peggy A. (My University, 1984)
Thirteen boys and 12 girls were assessed for peak VO2 and the distance covered in a 9 min run yds). Wt (kg), ht (cm), and age were also examined. Individual data for the boys and girls were substituted into predictive equations to predict peak vo2 developed by Baldwin (1983)and Kreun (1984), respectively. A dependent t-test, r, and% error were the statistical treatments utilized to determine validity.
Keywords: Exercise, Physiological aspects.; Exercise for children